Dinamika Pemikiran Keislaman Ikhwan Mantan Preman di Kelurahan Semanggi Surakarta - Warsito, W. (LP2M IAIN kUDUS, 2018)
The term hoodlum is associated with vicious activities while ikhwan is associated with religious activities. Phenomenon appeared when religious activities conducted by ikhwan eks hoodlum. This phenomenon appeared in Mojo village, Semanggi, Pasar Kliwon, Surakarta. This village had bad history. Any kind of bad activities were found in this village but the social life changed since 1999. The villagers agreed to close three prostitution locations in this village. Then, Islamic invitation came to hoodlums, step by step, their lives changed to be better. Researcher divides their lives into three periods. First, they were being good Muslims; second, they joined to lascar activities, third, the period after the general leader of lascars died. Based on this reality, researcher focused this study on the Islamic understanding of ikhwan eks hoodlum, some factors that shaped their understandings, and the impacts of their Islamic understandings. This study used qualitative method with interactiosme symbolic approach. This theory said that human being activities based on their symbol understanding. This understanding was formed by social interacts. To support this method, the writer used social learned and Islamic invitation (dakwah) that shaped their Muslim personalities. Among three periods, lascar period took more proportions. They joined sweeping violent activities and they against many hoodlums physically. These activities made many hoodlums areas be Islamic village. Apart from that, second period have produced extreme thought of some ikhwan.